Challenges, progress and prospects in solid state triplet fusion upconversion. Issue 20 (10th May 2022) - Alves, Jessica; Feng, Jiale; Nienhaus, Lea; Schmidt, Timothy W.
Abstract : Photon upconversion (UC) stands for the conversion of low to high energy photons, a promising approach to improve solar cells. While high efficiencies can be obtained in liquid UC, will a solid UC device be able to reach such levels? Abstract : Many applications, including solar energy conversion, can be enhanced by the upconversion of low energy photons. A flexible approach towards achieving this is by sensitized triplet–triplet annihilation, or triplet fusion. Despite high efficiencies being achieved for many compositions in solution, this has not yet been translated to the solid state. In this perspective, we provide an overview of the various approachesto obtain triplet fusion upconversion in solid state and discuss the challenges inherent to its implementation. Finally, we outlay our view on target areas to successfully envision solid state upconversion in the future.